Zinc Status in Patients with Sickle Cell Disease in Gezira State (Central Sudan) - Elmanon Elta, Mohammed Atta; Haroun Adam, Huda Mohammed; Ali Khalild, Khalid Eltom; Abdalla Mohammed, Badr Eldin Elsonni (مجلة الجزيرة للعلوم الصحية; مجلد 4 عدد 2 (2008), 2008)
Introduction                   Sickle cell disease is inherited as an autosomal recessive manner . HbS differs from HbA in the substitution of valine for glutamic acid in the sixth position of the b-globin chain. Heterozygous state for the HbS gene. Comprises 25-45% of the total hemoglobin, the rest being Hb-A, Hb-A 2 and Hb-F. .      Zinc status in children with sickle cell disease was determined in 1975, the finding, showed that there was  a significant decrease in zinc level in plasma, erythrocyte and hair. However, urinary zinc excretion was increased in sickle cell disease patients and is associated with decreased linear growth, skeletal growth, and muscle mass and sexual and skeletal maturation.  . Information regarding zinc status in sickle cell disease in Sudanese subjects is needed.             The objective of this study was to determine the zinc status in patients with sickle cell disease in addition to other related parameters including Haemoglobin level, total white blood cells count, sickling test, and identification of malaria parasite in the blood in the patients and control group. Anthropometric measurements including body weight, body height, and body mass index were also conducted. Study Design:             This is a case control study designed to study zinc status in patients with Sickle Cell Disease attending Wad Medani Paediatric Teaching Hospital in Gezira State.             Forty four patients diagnosed as sickle cell disease by clinical features and laboratory investigations (Hb Electrophoresis) were enrolled in this study. Fifty normal subjects were taken as control group. Patients with malnutrition and other diseases were excluded. Results In the present  study the mean of serum zinc concentration in the patients group(40.8 ±20 µg/dl) was significantly lower than  control group (55.3 ±32.4 µg/dl) (P < 0.05). Haemoglobin concentration in patients (6.6 ± 0.9 g/dl) was significantly lower (P< 0.001) compared to control group (11.1±2.1 g/dl).  The result of this study also showed that the values of  TWBCs count for the patients group (16150 ± 8196 cell / µL) was significantly higher (P < 0.001) compared to control group (5750 ± 3537 cell / µL ). The mean body weight (16.3 ± 8.2 kg), body height (103 ± 26 cm), and BMIs (14.5 ± 1.9) in the patients were significantly lower compared to control group (23.7 ± 8.0 kg), (120 ± 17 cm), (16.1 ± 3.2) respectively  (P < 0.001). All patients showed negative blood film for malaria parasite with the exception of only one subject, while three subjects of control group showed positive blood film for malaria parasite Conclusion Zinc status in patients with sickle cell disease in central Sudan is significantly lower than that of control group. Patients had lower hemoglobin level, lower body weight and height, and higher total white blood cell count than control group. All patients showed negative blood film for malaria parasite with exception of only one subject, while three subjects of control group showed positive blood film for malaria parasite. Because of low zinc level in patients with sickle cell disease, zinc supplementation is recommended. Further studies are needed to see its effect on the different parameters